Flipped Learning Course Design Tool Kit - Kurban, Fell Caroline (MEF University, 2016)
Curriculum Design, Higher Education, Curriculum Theory, Learning And Teaching In Higher Education, Curriculum Development, Curriculum and Instruction, Flipped Classroom, Flipped learning.This presentation describes the theories and practice behind flipped learning course design at MEF University.
Keywords: Tolkit; Teaching In Higher Education; Curriculum Design; MEF Univeristy; Flipped Classroom; Flipped learning